2014
DOI: 10.11159/ijtan.2014.005
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Heat Transfer Performance of Nanofluids in a Flat Plate Solar Collector

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The researchers determined that Cu-water nanofluid is more useful in terms of improving the heat loss parameter. Ekramian et al [44] executed studies to evaluate parameters such as thermal transfer coefficients and thermal efficiency in a FPSC system using different nanofluids. The states of temperature and flow rate parameters on nano-liquids and pure water were examined and the results were compared.…”
Section: Materials and Methods Utilization Of Nanofluids In Solar Collementioning
confidence: 99%
See 1 more Smart Citation
“…The researchers determined that Cu-water nanofluid is more useful in terms of improving the heat loss parameter. Ekramian et al [44] executed studies to evaluate parameters such as thermal transfer coefficients and thermal efficiency in a FPSC system using different nanofluids. The states of temperature and flow rate parameters on nano-liquids and pure water were examined and the results were compared.…”
Section: Materials and Methods Utilization Of Nanofluids In Solar Collementioning
confidence: 99%
“…The use of nanofluid has been very beneficial in terms of transmitting the heat parameter through the pipe in the collector. [44] MWCNT, CuO, Al2O3-H2O…”
Section: Materials and Methods Utilization Of Nanofluids In Solar Collementioning
confidence: 99%
“…Moghadam et al [17], Ekramian et al [18], and Shafiey et al [19] analyzed CuO-water-based nanofluid impact on a solar collector in comparison to water. The outcomes showed that an increase in the mass fraction of nanofluid decreases the specific heat.…”
Section: Introductionmentioning
confidence: 99%
“…Among the applications that are widely used are solar water heating systems, where solar radiation is converted into heat transmitted to the flowing water for heating. The most common collector types for solar water heating systems are flat plate solar collectors [2]. The standard flat plate solar collector consists of an insulation box with a high conductivity metal plate inside it, such as aluminium or copper called absorber plate, connected to the absorber plate tubes, and sometimes the tubes are integrated with the plate.…”
Section: Introductionmentioning
confidence: 99%